1987
DOI: 10.1128/jcm.25.2.423-424.1987
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugation-shell vial technique for rapid detection of herpes simplex virus cytopathic effect in Vero cells

Abstract: A centrifugation-shell vial technique for herpes simplex virus detected the virus in 50 (24.6%) of 203 specimens by cytopathic effect at 48 h, compared with detection of the virus in 47 (23.2%) specimens by immunofluorescence at 24 h. The rapid detection of cytopathic effect may be useful to laboratories that are not interested in typing all herpes simplex virus specimens but that wish to reduce the cost of herpesvirus cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Darougar et al (2), using an SVC assay with HEp-2 cells stained at 48 h by an indirect polyclonal fluorescent-antibody stain, detected 54 positive specimens compared with the 24 detected by an HEp-2 conventional culture when screening 2,100 cervical cultures from randomly selected women. In this last study, a major difference was the speed of centrifugation of 15,000 x g, which is well above the 700 x g and 3,500 x g used by us and other investigators (4,7,8).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Darougar et al (2), using an SVC assay with HEp-2 cells stained at 48 h by an indirect polyclonal fluorescent-antibody stain, detected 54 positive specimens compared with the 24 detected by an HEp-2 conventional culture when screening 2,100 cervical cultures from randomly selected women. In this last study, a major difference was the speed of centrifugation of 15,000 x g, which is well above the 700 x g and 3,500 x g used by us and other investigators (4,7,8).…”
Section: Discussionmentioning
confidence: 69%
“…The shell vial centrifugation culture (SVC) technique for the detection of HSV has significantly added to our ability to detect this virus accurately and rapidly (within 24 h). To date, this technique shows great promise when used with HEp-2 (2), mink lung (8), MRC-5 (4), and Vero (7) cells. However, in our experience and that of others, primary rabbit kidney (PRK) cells have proven to be the most sensitive and rapid cell line for HSV detection when used in a conventional tissue culture format (1,3,6).…”
mentioning
confidence: 99%
“…A method combining cell culture and staining is the shell vial centrifugation method. This technique detects HSV within 16 to 48 h after inoculation (49,114,120,154). Serologic examination is of no assistance is diagnosing neonatal infection due to HSV (6,119).…”
Section: Herpesvirusesmentioning
confidence: 99%
“…(2), Pruneda and Almanza (8), and Salmon et al (9) used a spin-amplified adsorption procedure to detect most HSV isolates within 16 to 48 h of culture initiation. Michalski et al (5) reported a sensitivity of 97.6% for detection of HSV isolates when specimens were adsorbed onto tissue culture by the spin-amplified procedure and detected by a commercial ELISA within 2 days of specimen set-ups.…”
Section: Notes 2197mentioning
confidence: 99%
“…Cytomegalovirus replication could be detected within 2 days by immunostaining with monoclonal antibody to an early antigen of cytomegalovirus. The rapid recovery of HSV has also been reported with centrifugation and immunodiagnostic detection (2,5,8,9). However, all these investigators have used shell vials or flat-bottomed culture tubes for their centrifuge-mediated viral adsorptions.…”
mentioning
confidence: 99%